Atmospheric Boundary Layer Processes, Characteristics and Parameterization - Li, Yubin; Tang, Jie (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the variation characteristics, dynamical processes, and their parameterization methods in the atmospheric boundary layer. The atmospheric boundary layer is of great importance in affecting the weather, air quality, and climate change. This reprint reports new observation findings of the atmospheric boundary layer over underlying surfaces of megacity, desert, and ocean, and also presents new methods of atmospheric boundary layer parameterization and modelling.